Status Gizi Atlet Bola Basket Klub Rongqing Banjarmasin - Kasanrawali, Andi; Habibie, Muhammad; Prayoga, Hegen Dadang; Nurulita, Retno Farhana (Jurnal Porkes, 2024)
The problem of this study was to determine the nutritional status of basketball athletes at the Rongqing Banjarmasin club. This study aims to examine the nutritional status of basketball athletes of the Rongqing Banjarmasin club. The research method used is descriptive survey method with data collection through observation, interviews, and documentation. Height and weight measurements were taken to determine the athlete's Body Mass Index (BMI). The population and sample of this study were all Rongqing Club players, as many as 20 people and using total sampling. The results showed that the majority of athletes, namely 75.0% (15 people), had normal nutritional status. A total of 15.0% (3 people) were classified as thin (mild weight loss), 10.0% (2 people) were classified as fat (mild weight gain), and there were no athletes who had a very fat nutritional status (severe weight gain). The maximum value of BMI obtained is 75.0, the minimum value is 10.0, with an average of 33.33 and a standard deviation of 29.52. The conclusion of this study shows that most athletes have a good nutritional status, which is important to support athletes' fitness, health, and performance.